Ovum Pick-Up and Ovaries Characterization of Black Bengal Goat from Slaughterhouse - Nourin, Shobhana; Mohit, Md. Muktafi bin; Zohara, Begum Fatema; Islam, Md. Faruk (Universitas Airlangga, 2024)
Black Bengal goat is the only indigenous breed in Bangladesh. These are small-sized goats renowned for their high-quality meat, skin, and adaptability to adverse environmental conditions. To conserve the originality of this species, it is mandatory to develop an effective methodology for their germ cells to be harvested after death. Therefore, the study was conducted to assess the ovarian status and evaluate the most suitable method of ovum pick-up as well as the characterization of ovum from slaughterhouse specimens. A total of 182 ovaries were collected from local slaughterhouses from June 2022 to July 2023 and grossly examined to assess their status. Two methods were used to retrieve oocytes from the ovaries: aspiration and slicing. The grading of the ovum was done based on the germ layer present surrounding the oocytes. From 182 ovaries, the rates of corpus luteum (CL), tumor, and cyst were found to be 14.29%, 6.59%, and 27.47%, respectively. In the aspiration method, the significantly highest percentage of recovery rate (38.89%) and grade A oocytes (51.06%) were found within 1–3 hours of slaughtering. In the slicing method, the significantly highest percentage of recovery rate (19.57%) and grade A (60.61%) oocytes were found within 1–3 hours of slaughtering. The recovery rate was significantly higher (34.1%) in the aspiration method than in the slicing method (17.1%). There was no significant relationship in oocyte quality between the two methods. The recovery rate was not significantly dependent on the presence of CL. In conclusion, the findings from this study may be useful for assessing the quality of oocytes to preserve the germ cells and utilize them for in vitro fertilization for conserving Black Bengal goat.